A Smart and Budget-Friendly Android Application for Motorcycle Safety and Engine Control System - Rakhmadi, Aris; Ihsan Adi, Mahfud; Ary Prasetya, Dedi; Muhammad; Faqih Dzulqarnain, Muhammad (Faculty of Information Technology, Universitas Tarumanagara, 2025)
Motorcycle theft remains a significant security issue, necessitating an affordable and effective solution. This study presents a cost-effective Android-based motorcycle security and engine control system using Arduino, integrating Bluetooth communication for remote operation. The system enables users to start the engine, activate an alarm, and monitor security conditions via a custom Android application, enhancing both security and convenience. The hardware consists of an Arduino Uno microcontroller, Bluetooth HC-05 module, and a four-channel relay module, allowing secure wireless control. System testing demonstrated stable Bluetooth connectivity up to 10 meters, low power consumption (150 mW for Bluetooth HC-05), and reliable command execution. A key advantage is its low cost, totaling approximately 223,000 IDR ( USD 15), making it significantly more affordable than conventional GPS-based security systems. Results confirm that the proposed system offers a low-cost yet effective alternative to traditional security methods, providing real-time monitoring, user-friendly operation, and enhanced theft prevention. However, limitations such as Bluetooth range constraints and potential security risks highlight areas for improvement. Future enhancements could include biometric authentication, GPS tracking, and cloud-based monitoring to strengthen security and scalability. By leveraging affordable components and smartphone integration, this study contributes to developing innovative, accessible, and cost-efficient motorcycle security solutions, improving vehicle protection for a wider audience.